Triterpenoid Saponins From the Fruit of Acanthopanax senticosus (Rupr. & Maxim.) Harms - Liu, Yan; Jiang, Peng; Zhang, Mei-Ling; Pan, Juan; Guan, Wei; Li, Xiao-Mao; Yang, Bing-You; Kuang, Hai-Xue (Frontiers in Chemistry, 2022)
Five previously undescribed oleanane-type triterpenoid saponins (1-5), together with twenty-four known saponins (6-29) were isolated from the fruit of Acanthopanax senticosus. The structures of all compounds were elucidated by extensive spectroscopic analysis, including 1D, 2D NMR, and HR-ESI-MS, in combination with chemical methods (acid hydrolysis). The neuroinflammation model was established by LPS-induced BV2 microglia, and the neuroprotective effects of all compounds (1-29) were evaluated.